Respuesta :

gmany
If (x - 2) is a factor of 2x³ + x² - 3 then for the value of x = 2 the polynominal is equal zero.
Substitute:
2 · 2³ + 2² - 3 = 2 · 8 + 4 - 3 = 16 + 4 - 3 = 17 ≠ 0
Answer: B) (x - 2) is not a factor.

(x-2) is not a factor of the polynomial 2x³ + x² – 3. Then the correct option is B.

What is a factorization?

It is a method for dividing a polynomial into pieces that will be multiplied together. At this moment, the polynomial's value will be zero.

The polynomial is given below.

⇒ 2x³ + x² – 3

The factor of the polynomial will be

⇒ 2x³ + x² – 3

⇒ 2x³ + 3x² – 2x² – 3

⇒ x²(2x + 3) – 1(2x + 3)

⇒ (x² – 1)(2x + 3)

⇒ (x – 1)(x + 1)(2x + 3)

(x-2) is not a factor of the polynomial 2x³ + x² – 3.

Then the correct option is B.

More about the factorization link is given below.

https://brainly.com/question/6810544

#SPJ2